Practices and Tools for Servitization Managing Service Transition (Springer International Publishing, 2018)
This edited book intends to provide knowledge on tools and practices of servitization to facilitate the formulation and implementation of servitization-based strategies, service infusion and manufacturing service transition globally. Including 22 practically relevant contributions, this book aims to help scholars and practitioners seeking to facilitate servitization in companies through original perspectives and advanced thinking in related issues such as business models, strategic change, practices, processes, routines, value creation and appropriation. Employing practice theory as a useful frame, the contributions span theoretical approaches such as product-service systems, service science, services-dominant logic and cocreation, resource-based views, industrial organization and institutional theory. The book presents tools and frameworks to enable and support servitization and engender understanding of servitization-as-practice.